2021
DOI: 10.1007/s40520-021-01989-7
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the perception of nursing home practitioners about the implementation of quality indicators for drug consumption in nursing homes

Abstract: Introduction Nursing homes (NHs) are an ideal environment in which to implement interventions aimed at reducing inappropriate prescriptions. Quality indicators (QIs) may be useful to standardize practices, but it is unclear how they mediate change. In the framework of a quantitative study aimed at reducing the prescription of anticholinergic drugs among NH residents using QIs, we performed a qualitative study to describe the investigators’ perception of the utility of QIs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Of the 2530 retrieved studies, 193 were ultimately included 6,7,11–201 . The PRISMA-ScR diagram (Figure 1) shows the study selection process and reasons for full-text exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 2530 retrieved studies, 193 were ultimately included 6,7,11–201 . The PRISMA-ScR diagram (Figure 1) shows the study selection process and reasons for full-text exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…The added value of the collaboration between pharmacists and other healthcare professionals was already observed in nursing homes through a qualitative study. 6 The results showed that all healthcare professionals' collaborative analysis and review of older individuals' medicines and prescriptions positively impacted patient safety and drug expenditure ( 7 , 6 ). In addition, better knowledge about medicines and their adverse health outcomes was provided following mutual education among healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%